Functional rehabilitation of fractured root canal treated posterior tooth: A case report (Indian Journal of Case Reports, 2020)
The objective of dentists is to preserve the teeth back to its functional form at any cost based on the requirements and willingness of the patient. This case report emphasizes more on restoring fractured endodontically treated teeth, where the fracture had extended subgingivally deeper to the middle-third of the palatal root segment. Excluding all other restoration methods based on the challenges, the present case was treated using posterior high strength glass ionomer restoration for margin elevation in the radicular segment and miracle mix restoration on the coronal portion of the tooth. Finally, the porcelain fused crown covers the crown completely for further functional usage. The margin is the challenge in this defect management for saving the tooth back to its functional form according to the patient’s willingness.